Power systems’ performance under high renewables’ penetration rates: a natural experiment due to the COVID-19 demand shock - Francesco Pietro Colelli; Daan Witkop; Enrica De Cian; Massimo Tavoni (Environmental Research Letters, 2021)
COVID-19 lockdowns make it possible to investigate the extent to which an unprecedented increase in renewables’ penetration may have brought unexpected limitations and vulnerabilities of current power systems to the surface. We empirically investigate how power systems in five European countries have dealt with this unexpected shock, drastically changing electricity load, the scheduling of dispatchable generation technologies, electricity day-ahead wholesale prices, and balancing costs. We find that low-cost dispatchable generation from hydro and nuclear sources has fulfilled most of the net-load even during peak hours, replacing more costly fossil-based generation. In Germany, the UK, and Spain coal power plants stood idle, while gas-fired generation has responded in heterogeneous ways across power systems. Falling operational costs of generators producing at the margin and lower demand, both induced by COVID-19 lockdowns, have significantly decreased wholesale prices. Balancing and other ancillary services’ markets have provided the flexibility required to respond to the exceptional market conditions faced by the grid. Balancing costs for flexibility services have increased heterogeneously across countries, while ancillary markets’ costs, measured only in the case of Italy, have increased substantially. Results provide valuable evidence on current systems’ dynamics during high renewables’ shares and increased demand volatility. New insights into the market changes countries will be facing in the transition towards a clean, secure, and affordable power system are offered.